Outcomes of Pregnancies After Kidney Transplantation: Lessons Learned From CKD. A Comparison of Transplanted, Nontransplanted Chronic Kidney Disease Patients and Low-Risk Pregnancies. Issue 10 (October 2017) - Piccoli, Giorgina Barbara; Cabiddu, Gianfranca; Attini, Rossella; Gerbino, Martina; Todeschini, Paola; Perrino, Maria Luisa; Manzione, Ana Maria; Piredda, Gian Benedetto; Gnappi, Elisa; Caputo, Flavia; Montagnino, Giuseppe; Bellizzi, Vincenzo; et al.
Abstract : Background: Kidney transplantation (KT) may restore fertility in chronic kidney disease (CKD). The reasons why maternofetal outcomes are still inferior to the overall population are only partially known. Comparison with the CKD population may offer some useful insights for management and counselling. Aim of this study was to analyse the outcomes of pregnancy after KT, compared with a large population of nontransplanted CKD patients and with low-risk control pregnancies, observed in Italy the new millennium. Methods: We selected 121 live-born singletons after KT (Italian study group of kidney in pregnancy, national coverage about 75%), 610 live-born singletons in CKD, and 1418 low-risk controls recruited in 2 large Italian Units in the same period (2000-2014). The following outcomes were considered: maternal and fetal death; malformations; preterm delivery; small for gestational age (SGA) baby; need for the neonatal intensive care unit; doubling of serum creatinine or increase in CKD stage. Data were analyzed according to kidney diseases, renal function (staging according to CKD-epidemiology collaboration), hypertension, maternal age, parity, ethnicity. Results: Maternofetal outcomes are less favourable in CKD and KT as compared with the low-risk population. CKD stage and hypertension are important determinants of results. Kidney transplantation patients with estimated glomerular filtration rate greater than 90 have worse outcomes compared with CKD stage 1 patients; the differences level off when only CKD patients affected by glomerulonephritis or systemic diseases ("progressive CKD") are compared with KT. In the multivariate analysis, risk for preterm and early-preterm delivery was linked to CKD stage (2-5 vs 1: relative risk 3.42 and 3.78) and hypertension (RR 3.68 and 3.16) while no difference was associated with being a KT or a CKD patient. Conclusions: The maternofetal outcomes in patients with kidney transplantation are comparable with those of nontransplanted CKD patients with similar levels of kidney function impairment and progressive and/or immunologic kidney disease. Abstract : The outcomes of pregnancy after kidney transplantation (KT) are compared with nontransplanted chronic kidney disease (CKD) patients and with low-risk control pregnancies and materno-fetal outcomes are comparable between KT and nontransplanted CKD patients, but less favorable in CKD and KT than the low-risk population. Supplemental digital content is available in the text.